2022
DOI: 10.1590/1519-6984.242301
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activities of silver nanoparticles synthesised using the seed extracts of three varieties of Phoenix dactylifera

Abstract: Green synthesis of silver nanoparticles (AgNPs) is an ecofriendly, cost-effective and promising approach for discovery of novel therapeutics. The aim of the current work was to biogenic synthesize, characterize AgNPs using seed extracts of three economically important varieties of date palm (Iklas, Irziz and Shishi), and assess their anti-pathogenic bacterial activities. AgNPs were synthesised then characterised using electron microscopy and Fourier transform infrared analyses. The bactericidal activities of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(36 reference statements)
0
5
0
1
Order By: Relevance
“…As nanopartículas metálicas apresentam comportamento óptico observável em decorrência da forma e tamanho, isto proporciona absorções em regiões distintas do espectro visível denominadas bandas plasmons que é a Ressonância de Plasmons de Superfície (RPS). Quanto à estabilização e as dimensões das nanopartículas encontradas, os resultados convergem com estudos publicados sobre a formação de nanopartículas de prata e citrato (Aldayel et al, 2022).…”
Section: Resultsunclassified
“…As nanopartículas metálicas apresentam comportamento óptico observável em decorrência da forma e tamanho, isto proporciona absorções em regiões distintas do espectro visível denominadas bandas plasmons que é a Ressonância de Plasmons de Superfície (RPS). Quanto à estabilização e as dimensões das nanopartículas encontradas, os resultados convergem com estudos publicados sobre a formação de nanopartículas de prata e citrato (Aldayel et al, 2022).…”
Section: Resultsunclassified
“…Hence, synthesis of metal nanoparticles using green methods having antibacterial potential has become an alternative remedy for pathogens control. Various studies have reported that metal nanoparticles strongly inhibit the growth of pathogens due to disruption of plasma membrane which eventually leads to death of bacterial cells (Aldayel et al, 2022;Shah et al, 2021). Among metal nanoparticles of same nature, Zinc oxide nanoparticals are one of the most effective and safe antimicrobial agents which are being used as medicine as well as preservative in packaging since long (Baum et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…S. typhi , E. coli ATCC 8739, and methicillin-resistant Staphylococcus aureus (MRSA) bacterial strains were acquired from King Faisal University’s College of Medicine. The disc diffusion assay was carried out in accordance with Aldayel et al, 2021 , Aldayel et al, 2022 , and Rana et al (2023) and nutrient broth was used for the cultivation of all microbial strains (Sigma Aldrich, Cat. no.…”
Section: Materials and Methodologymentioning
confidence: 99%